Roles of insulinlike growth factor 1 (IGF-1) and the IGF-1 receptor in epidermal growth factor-stimulated growth of 3T3 cells. - Pietrzkowski, Z (1992)
BALB/c3T3 cells are exquisitely growth regulated and require platelet-derived growth factor, epidermal growth factor (EGF), and insulinlike growth factor 1 (IGF-1) for growth. When BALB/c3T3 cells are transfected with plasmids constitutively expressing both EGF and the human IGF-1 receptor mRNAs, the cells are capable of growing in serum-free medium without the addition of any exogenous growth factor. These cells, called p5 cells, can grow for prolonged periods in serum-free medium. BALB/c3T3 cells transfected with only the IGF-1 receptor expression plasmid (p6 cells) do not grow in serum-free medium but do grow if IGF-1 (or insulin in supraphysiological concentrations) is added. p6 cells also grow in response to EGF, confirming that the combination of EGF and an overexpressed IGF-1 receptor is sufficient for the growth of 3T3 cells. We have found that in EGF-stimulated p6 cells there is an increase in the expression of IGF-1 mRNA, that IGF-1 is secreted into the medium, and that the growth of p5 cells and EGF-stimulated p6 cells is inhibited by exposure to antisense oligodeoxynucleotides to IGF-1 receptor RNA. Finally, while cells constitutively expressing both EGF and EGF receptor RNAs grow, albeit modestly, in serum-free medium, their growth is also inhibited by an antisense oligodeoxynucleotide to IGF-1 receptor RNA. In contrast, in cells overexpressing the IGF-1 receptor, IGF-1-mediated cell growth occurs independently of the platelet-derived growth factor and EGF receptors (Z. Pietrzkowski, R. Lammers, G. Carpenter, A. M. Soderquist, M. Limardo, P. D. Phillips, A. Ullrich, and R. Baserga, Cell Growth Differ. 3:199-205, 1992, and this paper). These data indicate that an important role for EGF is participation in the activation of an autocrine loop based on the IGF-1-IGF-1 receptor interaction, which is obligatory for the proliferation of 3T3 cells.